Family aggregation of human T-lymphotropic virus 1-associated diseases: A systematic review - Alvarez C. (2016)
Human T-lymphotropic virus 1 (HTLV-1) is a retrovirus that produces a persistent infection. Two transmission routes (from mother to child and via sexual intercourse) favor familial clustering of HTLV-1. It is yet unknown why most HTLV-1 carriers remain asymptomatic while about 10% of them develop complications. HTLV-1 associated diseases were originally described as sporadic entities, but familial presentations have been reported. To explore what is known about family aggregation of HTLV-1-associated diseases we undertook a systematic review. We aimed at answering whether, when, and where family aggregation of HTLV-1-associated diseases was reported, which relatives were affected and which hypotheses were proposed to explain aggregation. We searched MEDLINE, abstract books of HTLV conferences and reference lists of selected papers. Search terms used referred to HTLV-1 infection, and HTLV-1-associated diseases, and family studies. HTLV-1-associated diseases considered are adult T-cell leukemia/lymphoma (ATLL), HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP), HTLV-1-associated uveitis, and infective dermatitis. Seventy-four records reported HTLV-1-associated diseases in more than one member of the same family and were included. Most reports came from HTLV-1-endemic countries, mainly Japan (n = 30) and Brazil (n = 10). These reports described a total of 270 families in which more than one relative had HTLV-1-associated diseases. In most families, different family members suffered from the same disease (n = 223). The diseases most frequently reported were ATLL (115 families) and HAM/TSP (102 families). Most families (n = 144) included two to four affected individuals. The proportion of ATLL patients with family history of ATLL ranged from 2 to 26%. The proportion of HAM/TSP patients with family history of HAM/TSP ranged from 1 to 48%. The predominant cluster types for ATLL were clusters of siblings and parent-child pairs and for HAM/TSP, an affected parent with one or more affected children. The evidence in the literature, although weak, does suggest that HTLV-1-associated diseases sometimes cluster in families. Whether familial transmission of HTLV-1 is the only determining factor, or whether other factors are also involved, needs further research.